-13rs-12s+6rs=

Simple and best practice solution for -13rs-12s+6rs= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13rs-12s+6rs= equation:


Simplifying
-13rs + -12s + 6rs = 0

Reorder the terms:
-13rs + 6rs + -12s = 0

Combine like terms: -13rs + 6rs = -7rs
-7rs + -12s = 0

Solving
-7rs + -12s = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '12s' to each side of the equation.
-7rs + -12s + 12s = 0 + 12s

Combine like terms: -12s + 12s = 0
-7rs + 0 = 0 + 12s
-7rs = 0 + 12s
Remove the zero:
-7rs = 12s

Divide each side by '-7s'.
r = -1.714285714

Simplifying
r = -1.714285714

See similar equations:

| 4(x+1)=3x-4(6-x)+8 | | 4(2w-1)=-10+50 | | a(bx-c)=d-(x-e) | | 2(x+2)+3(3x+1)=57 | | 9-2-5n+4n= | | -20=-2(4+2y) | | 42-8x=-2x | | 20=7x+8+5x | | 5y-7y=-9 | | 6x-2(2x+4)=12 | | 2d-9-8d= | | 2x^3+4x^2+625=0 | | -2y+4=8y-b | | N-(n-7)=4 | | 31x-41+1=19 | | 4(4x+3)+25=11x-3 | | x^2+5*y^2=0 | | 7y+68=y+14 | | 11+x=57 | | 12.3+5.013d=5.015 | | -44+9d=5d | | 5(y+8)=7y+40 | | x+3(x-2)=2 | | 6(6-4x)=-84 | | 18x+9y=8 | | 4(8-2x)=32 | | 12+2y=1-y-12 | | x+3(4-2x)=x-2 | | 4+3-2= | | 12=156 | | x-30=3(x)-14 | | (X-4)-3(2x+3)=12x-8 |

Equations solver categories